Biomass partition and nutrient demand of coffee in different conditions and fertilization according to nutrient demand from simultaneous sinks - fruits and vegetative growth - Souza, Laís Teles de (2022)
Nutrient use efficiency is a big challenge to reduce costs and save resources. One way to enhance this efficiency is to apply nutrients at the right rate, which requires knowing the plant nutrient demand based on its produced biomass. However, the biomass and nutrient demand can vary according to factors such as fruit load, age, pruning management, plant density, cultivar, location, irrigation use, etc. Therefore, in the last few years, we have studied the coffee (Coffea Arabica L.) nutrient demand regarding the biomass produced to improve coffee fertilization strategies. We developed several experiments to measure the biomass produced and plant nutrient demand under different conditions. Here, we present the studies with coffee orchards in the first production cycle and with pruning branches. Furthermore, we developed a fertilization method - EsalqCafé - for arabica coffee based on nutrient demand data from preliminary research that considers the nutrient demand of the two simultaneous sinks (fruit load and the active vegetative growth) and we fertilize mature coffee orchards comparing with official fertilization methods to validate the EsalqCafé method. The first study was carried out in a coffee orchard in the first production cycle to measure the effect of fruit load on vegetative growth and nutrient demand. The experimental design was in randomized blocks with controlled fruit load in five levels and eight replicates. This study revealed that a high fruit load decreases vegetative biomass about three-fold, considering that the plant no longer produces 0.43 g of vegetation dry matter for each gram of fruit produced. The nutrient concentrations in the vegetative and fruiting tissues were not dependent on the fruit load and the nutrient demand varied according to the fruit load. The second study was carried out on coffee plants with plagiotropic branches pruned to determine the annual vegetative biomass and the macronutrient demand in rainfed and irrigated management. The experimental design was completely randomized with two treatments (rainfed and irrigated) and eleven replicates. Vegetative biomass and its macronutrient concentrations were measured to predict nutrients accumulated in vegetative biomass and total nutrient demand. Under rainfed or irrigated management, the vegetative biomass growth and nutrient concentrations did not vary. However, there was a satisfactory amount of rain during the growth cycle. The nutrient demand was the same for irrigated and rainfed management. Potassium, nitrogen and calcium were the nutrients most demanded, corresponding to 87% of the total macronutrient demand. The third study was carried out in three field experiments. The experiment design was in randomized blocks with four treatments, which were fertilization methods: EsalqCafé, Boletim 100 (1997), Boletim 100 updated version and 5ª Aproximação with five replications. The variables analyzed were: crop yield, nitrogen leaf concentration and phosphorus and potassium content in the soil at harvest time. Compared to existing fertilization methods, the results revealed the EsalqCafé was sufficient to supply the plant nutrient demand, maintaining nitrogen concentration in the leaf and the phosphorus and potassium content in the soil in the ideal range after harvest. However, further studies are needed.